Polymorphism and cyclodextrin inclusion complexes of antihypertensive agents - Mhlongo, Welcome Thabani (Department of Chemistry, 2026)
The objective of the project described in this thesis was to isolate polymorphs, solvates and cyclodextrin inclusion complexes of antihypertensive agents. The physical properties of different polymorphs of a given drug are of significant interest to the pharmaceutical industry. The solubility enhancement of poorly soluble drugs by encapsulating them within cyclodextrins is also an important pharmaceutical consideration. The drugs investigated were atenolol, metoprolol, oxprenolol free bases and two salts, namely oxprenolol hydrochloride and metoprolol tartrate. No polymorphs of these antihypertensive agents were isolated but metoprolol yielded a solvate with n-hexane. Single crystals of atenolol, metoprolol, metoprolol tartrate and oxprenolol were isolated and their X-ray structures are reported here for the first time. Inclusion complexes of atenolol, metoprolol and oxprenolol free bases with cyclodextrins were successfully investigated in the solid state. The cyclodextrin hosts used for drug inclusion were P-cyclodextrin, y-cyclodextrin, heptakis(2,6-di-O-methyl)-P-cyclodextrin, heptakis(2,3,6-tri-O-methyl)-P-cyclodextrin and exakis(2,3,6-tri-O-methyl)-acyclodextrin. A new crystal form of heptakis(2,3,6-tri-0-methyl)-P-cyclodextrin as a trihydrate was isolated in an attempt to produce an inclusion complex between this host compound and the drug substance atenolol. The first crystal form of this host compound, a monohydrate, was previously discovered by the Supramolecular Chemistry Research Unit at the University of Cape Town. The various analytical techniques utilised for the characterisation of the solid-state properties of the species were elemental analysis as well as thermal, X-ray diffraction and spectroscopic techniques. Single crystal X-ray diffraction was the principal technique used for investigation of structural features. The structure of metoprolol revealed one molecule per asymmetric unit while the structure of the metoprolol solvate revealed eight molecules of metoprolol and one of n-hexane per asymmetric unit. Structure solution was successful for six cyclodextrin inclusion complexes. The oxprenolol guest molecule was successfully modelled in P-cyclodextrin and heptakis(2,3,6-tri-0-methyl)-P-cyclodextrin. Metoprolol was successfully modelled in hexakis(2,3,6-tri-O-methyl)-a-cyclodextrin but could not be modelled in heptakis(2,3,6- tri-O-methyl)-p-cyclodextrin and P-cyclodextrin due to its severe disorder. The computed powder X-ray diffraction (PXRD) patterns of the oxprenolol-˜- cyclodextrin (OXPRBCD) and atenolol-P-cyclodextrin (ATBCD) inclusion complexes were different from their experimental PXRD patterns. This indicated that phase transformation had occurred upon grinding the single crystals for each of these complexes. These two complexes crystallise in space group Pl [with unit cell parameters a˜ 18, b ˜15 and c ˜ 15 A]; thus, they are isostructural. However, their experimental PXRD patterns are different from each other. The comparison of these experimental PXRDs with published reference patterns for P-cyclodextrin complexes showed that grinding OXPRBCD transformed this material into a form crystallising in the space group P21 while grinding ATBCD resulted in its transformation to a phase belonging to the space group C2. Such transformations have not been reported previously. Among the free bases studied, atenolol is the only one that is currently commercially available as a medicinal agent. Exploitation of metoprolol and oxprenolol free bases as guests for cyclodextrin inclusion has led to the isolation and full characterisation of new inclusion complexes that have potential for further pharmaceutical development.